BAHASA BALI SEBAGAI SIMBOL IDENTITAS MANUSIA BALI - Suastra, I Made (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 16 (2009): March 2009, 2009)
Abstract Undang-Undang dasar 1945 Pasal 32 ayat 2 and Undang-Undang Nomor 32 Tahun 2004 provide a vast opportunity for the local community to manage their capacity in every aspect of their life. In the application of the otonomy, local community has an opportunity to preserve their social cultural values as their identity of their community. Balinese can basically be recognised by their language (phonic form) they use as well as their traditions (physical forms) they practice. These aspects are commonly used as a symbol of identity by the Balinese ethnic community nationally and internationally. This symbol needs to be maintained for the shake of the Balinese community preservation. The purpose of this study is to explain the position of Balinese Language in the global era as a symbol of identity for the community. The study focuses on the description of the Balinese identity related to the Balinese language. One function of language is as symbol of identity. Balinese has this role for its community and it is also a pride. This condition can be proven by the development of the use of the Balinese language in time. At the present time Balinese has their function as a mean for expressing their cultural aspects. However, in this global era, the Balinese language develops naturally in line with the need of the user. The internal as well as the external problems of the language use in Balinese community need to be identified in order to find out the solution for maintaining the language, in turn the language itself is still continually function as a symbol of Balinese community.